2001
DOI: 10.1038/35087069
|View full text |Cite
|
Sign up to set email alerts
|

Nicastrin binds to membrane-tethered Notch

Abstract: The presenilins and nicastrin, a type 1 transmembrane glycoprotein, form high molecular weight complexes that are involved in cleaving the beta-amyloid precursor protein (betaAPP) and Notch in their transmembrane domains. The former process (termed gamma-secretase cleavage) generates amyloid beta-peptide (Abeta), which is involved in the pathogenesis of Alzheimer's disease. The latter process (termed S3-site cleavage) generates Notch intracellular domain (NICD), which is involved in intercellular signalling. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 31 publications
11
109
0
Order By: Relevance
“…Therefore, Notch and APP have distinct ␥-secretase pathways. Our conclusion is consistent with earlier studies that showed that APP and Notch do not compete for ␥-secretase activity in the cell (44,45). A lack of competition between the two substrates could arise because the processing of Notch and APP occurs in different subcellular compartments, or because the concentration of both substrates is not saturated.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, Notch and APP have distinct ␥-secretase pathways. Our conclusion is consistent with earlier studies that showed that APP and Notch do not compete for ␥-secretase activity in the cell (44,45). A lack of competition between the two substrates could arise because the processing of Notch and APP occurs in different subcellular compartments, or because the concentration of both substrates is not saturated.…”
Section: Discussionsupporting
confidence: 82%
“…Deletions within the ectodomain of NCT have been shown to block interactions with PS1 as judged by coimmunoprecipitation and to reduce or ablate ␥-secretase activity (17,31,41,42). It is not possible to conclude if these results are due to the genetic deletion of residues or regions in NCT that are needed for specific interactions with one or more ␥-secretase components, or if they are due to gross misfolding of the modified NCT constructs.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, we sought a homolog of hNCT that would fulfill this requirement and found one in the form of ceNCT. Genetic evidence indicates that ceNCT has functions that are broadly similar to those of its human counterpart, particularly with regards to ␥-secretase-mediated cleavage of Notch (11,17,26,42). In addition, while sharing only 21% amino acid identity, the large majority of Cys residues are conserved between the two molecules, suggesting a conserved overall structure.…”
Section: Discussionmentioning
confidence: 91%
“…Nicastrin, an integral component of the γ-secretase complex, is a transmembrane glycoprotein with a long hydrophilic N-terminal domain containing multiple glycosylation sites, a hydrophobic transmembrane domain and a short hydrophilic C-terminal tail [6,55]. Nicastrin was first identified in a C. elegans genetic screen as aph-2, an essential component of GLP-1/ Notch signaling pathway in early embryos [16].…”
Section: Introductionmentioning
confidence: 99%